PEMAKNAAN GURU TERHADAP BUDAYA DISIPLIN SEBAGAI FAKTOR PEMBENTUK KINERJA DI SDN DERMO I BANGIL - Muzamil Lubis; Ahmad Thohirin; M. Furqon Wahyudi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to explore teachers’ interpretations of disciplinary culture as a factor shaping performance at SDN Dermo I Bangil. The phenomenon of teacher discipline in elementary education is often viewed from an administrative perspective, yet it carries deeper meanings related to moral values and professional identity. This research employed a qualitative phenomenological approach, focusing on the lived experiences of teachers in internalizing and practicing discipline within their professional environment. Data were collected through semi-structured interviews, participant observation, and document analysis, involving three key informants—grade 2, 4, and 5 teachers—selected using purposive sampling. Data analysis followed the interactive model of Miles and Huberman, revealing four main themes: (1) discipline as a moral and professional value, (2) disciplinary culture as the school’s collective identity, (3) discipline as a driver of teacher performance and student order, and (4) challenges in balancing administrative demands with intrinsic motivation. Discipline was perceived not merely as compliance with rules but as a form of moral responsibility and an expression of dedication to the teaching profession. The findings indicate that a morally grounded disciplinary culture plays a central role in sustaining teacher performance and school effectiveness. Theoretically, this study extends the understanding of meaning-making within educational organizational culture.